Modifikasi dan uji performansi mesin perontok lada dengan mekanisme perontok silinder berjaring - Leo Dedy Anjiu; Suhendra Suhendra (TURBO [Tulisan Riset Berbasis Online], 2021)
Pepper is one of Indonesia's leading agricultural products. However, post-harvest handling of pepper, such as the threshing process, is still done traditionally. Efforts to overcome these problems done by developing a mechanical threshing process, including by designing and construction a mesh thresher cylinder type of pepper threshing. Test results show, this pepper thresher has a weakness, namely low threshing efficiency so that it needs to developed. Based on these conditions, research is needed that aims to develop, modify and done performance tests on the pepper thresher. The modification was made by making the contact angle between the thresher cylinder and the threshing net is 60o and resulted length of the threshing contact field of about 5.23 cm. The independent variable was the thresher cylinder rotational speed varied into 540, 471, 451 and 352 rpm. The dependent variables were capacity, threshing efficiency and percentage pepper of damage. The results of the analysis showed that the rotational speed of the threshing mechanism had a very significant effect on the capacity, threshing efficiency and the percentage pepper of damage. Increasing the speed of the thresher cylinder can increase the capacity and percentage of damaged pepper, but reduce threshing efficiency. The threshing efficiency increase of the pepper thresher before and after modification was from 35.8% to 95.93% on the approaching treatment.